STRATEGI PENGGUNAAN TEKNOLOGI DIGITAL UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN - Nailati, Raudah; Mutmainnah; Taswira, Ainun; Ibrahim; Nawir, Muhammad; Muhajir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology in the 21st century has fundamentally transformed the educational landscape, particularly following the experience of distance learning during the COVID-19 pandemic, which accelerated the massive adoption of various digital tools and platforms. This paper aims to examine strategies for utilizing digital technology to enhance learning effectiveness. The discussion covers basic concepts, theoretical foundations such as constructivism, connectivism, and the TPACK and SAMR frameworks, types of applicable technologies, integration strategies, implementation barriers, and methods for evaluating effectiveness. This study reveals that the availability of technology alone is insufficient; successful learning outcomes depend heavily on the teacher’s ability to integrate technology with subject matter and appropriate teaching methods. Effective strategies include aligning technology with learning objectives, implementing blended learning models, and utilizing interactive and adaptive features. In Indonesia, key challenges involve infrastructure gaps and disparities in digital competence across regions. This paper concludes that digital technology serves as a powerful supporting tool for creating meaningful, inclusive, and relevant learning, provided it is applied strategically in accordance with sound pedagogical principles.